Efeitos imuno-reguladores do Lactococcus Lactis produtor de HSP65 na artrite experimental em camundongos - Guilherme Gusmao Silva (2016)
Rheumatoid arthritis (RA) is a systemic autoimmune disease in which inflammation of the joints determines its destruction and loss of mobility. There is no prevention or cure for RA, and the treatment is based on conventional anti-inflammatory, analgesic drugs restricted to symptoms control. The loss of tolerance resulting in pathogenic autoimmunity can be restored by ingestion of the target antigen. This procedure induces oral tolerance, and their therapeutic effects are well established in experimental models and clinical trials. However, the continuous intake of purified antigen is not always feasible as an alternative therapy. Hsp65 is a chaperonin essential to protein folding and response to cellular stress. The Hsp65 is also a known regulator of the immune response and inflammatory process. For direct delivery of Hsp65 to the mucosa, a recombinant Lactococcus lactis was constructed in a way to produce and secret Mycobacterium leprae Hsp65. The present study has shown that the therapy with Lactococcus lactis prevented a Collagen Induced Arthritis and a model of acute arthritis in mice. This preventive effect included inhibition of paw edema and joint inflammation associated with reduced levels of inflammatory cytokines and pathogenic autoantibodies and augmented numbers of regulatory B and T lymphocytes